Mathieu Functions and Hill’s Equation - 28.14 Fourier Series

From testwiki
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
28.14.E1 me ν ( z , q ) = m = - c 2 m ν ( q ) e i ( ν + 2 m ) z Mathieu-me 𝜈 𝑧 𝑞 superscript subscript 𝑚 subscript superscript 𝑐 𝜈 2 𝑚 𝑞 superscript 𝑒 imaginary-unit 𝜈 2 𝑚 𝑧 {\displaystyle{\displaystyle\mathrm{me}_{\nu}\left(z,q\right)=\sum_{m=-\infty}% ^{\infty}c^{\nu}_{2m}(q)e^{\mathrm{i}(\nu+2m)z}}}
\Mathieume{\nu}@{z}{q} = \sum_{m=-\infty}^{\infty}c^{\nu}_{2m}(q)e^{\iunit(\nu+2m)z}

Error
Sqrt[2]*MathieuC[\[Nu], q, z] == Sum[(Subscript[c, 2*m])^\[Nu][q]* Exp[I*(\[Nu]+ 2*m)*z], {m, - Infinity, Infinity}, GenerateConditions->None]
Missing Macro Error Failure - Skipped - Because timed out
28.14.E2 ce ν ( z , q ) = m = - c 2 m ν ( q ) cos ( ν + 2 m ) z Mathieu-ce 𝜈 𝑧 𝑞 superscript subscript 𝑚 subscript superscript 𝑐 𝜈 2 𝑚 𝑞 𝜈 2 𝑚 𝑧 {\displaystyle{\displaystyle\mathrm{ce}_{\nu}\left(z,q\right)=\sum_{m=-\infty}% ^{\infty}c^{\nu}_{2m}(q)\cos(\nu+2m)z}}
\Mathieuce{\nu}@{z}{q} = \sum_{m=-\infty}^{\infty}c^{\nu}_{2m}(q)\cos@@{(\nu+2m)z}

MathieuCE(nu, q, z) = sum((c[2*m])^(nu)(q)* cos((nu + 2*m)*z), m = - infinity..infinity)
MathieuC[\[Nu], q, z] == Sum[(Subscript[c, 2*m])^\[Nu][q]* Cos[(\[Nu]+ 2*m)*z], {m, - Infinity, Infinity}, GenerateConditions->None]
Failure Failure Error Skipped - Because timed out
28.14.E3 se ν ( z , q ) = m = - c 2 m ν ( q ) sin ( ν + 2 m ) z Mathieu-se 𝜈 𝑧 𝑞 superscript subscript 𝑚 subscript superscript 𝑐 𝜈 2 𝑚 𝑞 𝜈 2 𝑚 𝑧 {\displaystyle{\displaystyle\mathrm{se}_{\nu}\left(z,q\right)=\sum_{m=-\infty}% ^{\infty}c^{\nu}_{2m}(q)\sin(\nu+2m)z}}
\Mathieuse{\nu}@{z}{q} = \sum_{m=-\infty}^{\infty}c^{\nu}_{2m}(q)\sin@@{(\nu+2m)z}

MathieuSE(nu, q, z) = sum((c[2*m])^(nu)(q)* sin((nu + 2*m)*z), m = - infinity..infinity)
MathieuS[\[Nu], q, z] == Sum[(Subscript[c, 2*m])^\[Nu][q]* Sin[(\[Nu]+ 2*m)*z], {m, - Infinity, Infinity}, GenerateConditions->None]
Failure Failure Error Skipped - Because timed out
28.14.E4 q c 2 m + 2 - ( a - ( ν + 2 m ) 2 ) c 2 m + q c 2 m - 2 = 0 𝑞 subscript 𝑐 2 𝑚 2 𝑎 superscript 𝜈 2 𝑚 2 subscript 𝑐 2 𝑚 𝑞 subscript 𝑐 2 𝑚 2 0 {\displaystyle{\displaystyle qc_{2m+2}-\left(a-(\nu+2m)^{2}\right)c_{2m}+qc_{2% m-2}=0}}
qc_{2m+2}-\left(a-(\nu+2m)^{2}\right)c_{2m}+qc_{2m-2} = 0
a = λ ν ( q ) , c 2 m = c 2 m ν ( q ) formulae-sequence 𝑎 Mathieu-eigenvalue-lambda 𝜈 𝑞 subscript 𝑐 2 𝑚 superscript subscript 𝑐 2 𝑚 𝜈 𝑞 {\displaystyle{\displaystyle a=\lambda_{\nu}\left(q\right),c_{2m}=c_{2m}^{\nu}% (q)}}
q*c[2*m + 2]-(a -(nu + 2*m)^(2))*c[2*m]+ q*c[2*m - 2] = 0
q*Subscript[c, 2*m + 2]-(a -(\[Nu]+ 2*m)^(2))*Subscript[c, 2*m]+ q*Subscript[c, 2*m - 2] == 0
Skipped - no semantic math Skipped - no semantic math - -
28.14.E5 m = - ( c 2 m ν ( q ) ) 2 = 1 superscript subscript 𝑚 superscript superscript subscript 𝑐 2 𝑚 𝜈 𝑞 2 1 {\displaystyle{\displaystyle\sum_{m=-\infty}^{\infty}\left(c_{2m}^{\nu}(q)% \right)^{2}=1}}
\sum_{m=-\infty}^{\infty}\left(c_{2m}^{\nu}(q)\right)^{2} = 1

sum(((c[2*m])^(nu)(q))^(2), m = - infinity..infinity) = 1
Sum[((Subscript[c, 2*m])^\[Nu][q])^(2), {m, - Infinity, Infinity}, GenerateConditions->None] == 1
Skipped - no semantic math Skipped - no semantic math - -
28.14.E7 c - 2 m - ν ( q ) = c 2 m ν ( q ) superscript subscript 𝑐 2 𝑚 𝜈 𝑞 superscript subscript 𝑐 2 𝑚 𝜈 𝑞 {\displaystyle{\displaystyle c_{-2m}^{-\nu}(q)=c_{2m}^{\nu}(q)}}
c_{-2m}^{-\nu}(q) = c_{2m}^{\nu}(q)

(c[- 2*m])^(- nu)(q) = (c[2*m])^(nu)(q)
(Subscript[c, - 2*m])^(- \[Nu])[q] == (Subscript[c, 2*m])^\[Nu][q]
Skipped - no semantic math Skipped - no semantic math - -
28.14.E8 c 2 m ν ( - q ) = ( - 1 ) m c 2 m ν ( q ) superscript subscript 𝑐 2 𝑚 𝜈 𝑞 superscript 1 𝑚 superscript subscript 𝑐 2 𝑚 𝜈 𝑞 {\displaystyle{\displaystyle c_{2m}^{\nu}(-q)=(-1)^{m}c_{2m}^{\nu}(q)}}
c_{2m}^{\nu}(-q) = (-1)^{m}c_{2m}^{\nu}(q)

(c[2*m])^(nu)(- q) = (- 1)^(m)* (c[2*m])^(nu)(q)
(Subscript[c, 2*m])^\[Nu][- q] == (- 1)^(m)* (Subscript[c, 2*m])^\[Nu][q]
Skipped - no semantic math Skipped - no semantic math - -
28.14#Ex1 c 0 ν ( 0 ) = 1 superscript subscript 𝑐 0 𝜈 0 1 {\displaystyle{\displaystyle c_{0}^{\nu}(0)=1}}
c_{0}^{\nu}(0) = 1

(c[0])^(nu)(0) = 1
(Subscript[c, 0])^\[Nu][0] == 1
Skipped - no semantic math Skipped - no semantic math - -
28.14#Ex2 c 2 m ν ( 0 ) = 0 superscript subscript 𝑐 2 𝑚 𝜈 0 0 {\displaystyle{\displaystyle c_{2m}^{\nu}(0)=0}}
c_{2m}^{\nu}(0) = 0
m 0 𝑚 0 {\displaystyle{\displaystyle m\neq 0}}
(c[2*m])^(nu)(0) = 0
(Subscript[c, 2*m])^\[Nu][0] == 0
Skipped - no semantic math Skipped - no semantic math - -